Leading Academic Research: A Preliminary Study of Taiwan Social Sciences Citation Index–Listed Journals’ Policies Regarding Academic Ethics - Chien Chou; Sophia Jui-An Pan; Jui-Lien Lu (Journal of Library and Information Studies, 2022)
This study aims to explore the publishing policies and submission guidelines of 110 academic journals covered in the Taiwan Social Sciences Citation Index (TSSCI) during 2018 and 2019. Using document analysis, information regarding academic ethics and copyright are analyzed. The results indicate that most of the journals emphasize manuscript originality. In addition, about 40% of journals clearly indicates that authors are obliged to avoid plagiarism and provide proper and accurate citation. Less than 30% of journals specifically state the obligations and responsibilities of scholarly authors. More than 40% of journals set up regulations for co-authorship. Less than 30% of journals clearly state that authors need to make a conflict-of-interest disclosure. Still a few journals use vague or imprecise legal terms in their policies. Based on the results, this study further provides practical advice in academic publishing. Specific suggestions include providing complete submission instructions and revising them in a timely manner, reviewing journal publishing ethics and operating policy to keep in line with international practices, and formulating regulations in response to the various scholarship and journal publishing movements.(Article content in Chinese with English extended abstract)